DNA BARCODING: FOUNDATIONS AND APPLICATIONS FOR SOUTHEAST ASIAN FRESHWATER FISHES - Hadi Dahruddin; Renny Kurnia Hadiaty; Nicolas Hubert (Treubia, 2016)
Identifying and delineating species are the primary tasks of taxonomy. Owing to the decreasing interest of the nations for taxonomy and the inventory of living beings, funds have been drastically decreasing during the last two decades for taxonomic studies. As a consequence, the worldwide pool of taxonomists has dramatically decreased. DNA barcoding, as an automated tool for species delineation and identification, proved to rejuvenate the field of taxonomy and open new perspectives in ecology and conservation. In the present review, we will discuss how DNA barcoding established as a new paradigm in taxonomy and how DNA barcoding has been recently integrated in taxonomic studies. We will further detail the potential applications for species identifications and discuss how DNA barcoding may positively impact the inventory and conservation of living beings, particularly in biodiversity hotspots. We emphasise the benefit of DNA barcoding for the conservation of Southeast Asian freshwater fishes.